Attitudes of at-risk older adults about prevention of cardiovascular disease and dementia using eHealth: a qualitative study in a European context - Eric Moll van Charante; Edo Richard; Miia Kivipelto; A Jeannette Pols; Carol Brayne; Cathrien RL Beishuizen; Ulrika Akenine; Mariagnese Barbera; Anna Rosenberg; Mandana Fallah Pour; Hilkka Soininen; Francesca Mangialasche; et al. (BMJ Open)
Objectives Prevention of cardiovascular disease (CVD) and dementia is a key health priority among older adults. Understanding individuals’ attitudes to, the prevention of these conditions, particularly when delivered through novel eHealth tools, could help in designing effective prevention programmes. The aim of the study was to explore the attitudes of older adults at increased risk of CVD and dementia regarding engagement in eHealth self-management prevention programmes, and to describe the facilitators and barriers.Design A qualitative research approach was used. Data were collected through eight focus groups in Finland, France and the Netherlands. Data were analysed following the principles of grounded theory.Setting and participants Forty-four community-dwellers aged 65+ at risk of CVD were recruited from a previous trial cohort in Finland, and through general practices in France and the Netherlands.Results The study identified three categories: access to reliable information, trust in the healthcare providers and burden and stigma of dementia. A core category was also identified: the interactive process of the three categories influencing engagement in self-management prevention programme. The categories were interconnected through an interactive process and influenced by the local healthcare culture and context which shaped them differently, becoming either facilitators or barriers to engage in eHealth self-management prevention programmes.Conclusions The study emphasises the importance of considering the interactions between the identified categories in this study, grounded in the local healthcare culture and context in further developments of eHealth self-management interventions that aim to prevent CVD and dementia.Trial registration number ISRCTN48151589